Pengaruh Gaya Hidup dan Sertifikasi Halal terhadap Keputusan Pembelian Produk Perawatan Kecantikan Marketplace TikTokShop Mahasiswa Universitas Ibn Khaldun Bogor - Muhammad Fadil Riswandi; Kholil Nawawi; Nurman Hakim (Lembaga Yasin AlSys, 2025)
This study is grounded in the rising trend of social media-based marketplaces and the growing awareness among Muslim consumers regarding the importance of products that align with sharia principles. The objective of this research is to analyze the influence of lifestyle and halal certification on the purchasing decisions of beauty care products on the TikTok Shop platform among students of the Sharia Economics Program at Ibn Khaldun University, Bogor. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to active students from the 2021 to 2023 cohorts. Data analysis was conducted using multiple linear regression. The results indicate that lifestyle and halal certification have a significant simultaneous influence on purchasing decisions for beauty products. Partially, lifestyle exerts a dominant influence, while halal certification remains a significant factor in shaping consumer decisions. These findings suggest that marketing strategies targeting young Muslim consumers should consider lifestyle patterns alongside product halal compliance as added value. The implications of this research include the need to enhance consumer literacy regarding halal products and to strengthen business actors’ understanding of the dynamics of the halal market in the digital era.